Release Profile and Antibacterial Activity of Thymus sibthorpii Essential Oil-Incorporated, Optimally Stabilized Type I Collagen Hydrogels - Caglar Ersanli; Ioannis Skoufos; Konstantina Fotou; Athina Tzora; Yves Bayon; Despoina Mari; Eleftheria Sarafi; Konstantina Nikolaou; Dimitrios I. Zeugolis (Bioengineering)
Antimicrobial resistance is one of the drastically increasing major global health threats due to the misuse and overuse of antibiotics as traditional antimicrobial agents, which render urgent the need for alternative and safer antimicrobial agents, such as essential oils (EOs). Although the strong antimicrobial activity of various EOs has already been studied and revealed, their characteristic high sensitivity and volatility drives the need towards a more efficient drug administration method via a biomaterial system. Herein, the potential of Thymus sibthorpii EO incorporated in functionalized antibacterial collagen hydrogels was investigated. At first, the optimally stabilized type I collagen hydrogels via six different multi-arm poly (ethylene glycol) succinimidyl glutarate (starPEG) crosslinkers were determined by assessing the free amine content and the resistance to enzymatic degradation. Subsequently, 0.5, 1, and 2% v/v of EO were incorporated into optimized collagen hydrogels, and the release profile, as well as release kinetics, were studied. Finally, biomaterial cytocompatibility tests were performed. Thymus sibthorpii EO was released from the hydrogel matrix via Fickian diffusion and showed sustained release and 0.5% v/v EO-loaded hydrogels showed adequate antibacterial activity against Staphylococcus aureus and did not show any statistically significant difference compared to penicillin (p < 0.05). Moreover, none of the fabricated composite antibacterial scaffolds displayed any cytotoxicity on NIH-3T3 fibroblasts. In conclusion, this work presents an innovative antibacterial biomaterial system for tissue engineering applications, which could serve as a promising alternative to antibiotics, contributing to coping with the issue of antimicrobial resistance.